The effect of body mass index on neonatal outcomes in Chinese women with polycystic ovary syndrome - Guo, Haiyan; Wang, Bian; Gao, Hongyuan; Zhu, Qianqian (Frontiers in Medicine, 2022)
Purpose：To explore the effect of body mass index (BMI) on neonatal outcomes in patients with polycystic ovary syndrome following the frozen embryo transfer. Methods：This study included 1676 singletons born from PCOS mothers after FET during Jan 1, 2007 and Dec 31, 2019. BMI was categorized into three groups: underweight (BMI less than 18.5kg/m2), normal weight (BMI between 18.5 and 24.9kg/m2), and overweight (BMI between 25.0 and 29.9kg/m2). Logistic regression models with generalized estimating equations were used for clustering by patients to explore the effect of BMI on neonatal outcomes. Results: Compared with normal weight mothers, the rate of large for gestational age (LGA) baby (adjusted odds ratio [aOR] 0.45, 95% confidence interval [95%CI] 0.22-0.93) significantly decreased for underweight mothers and significantly increased (aOR 1.82, 95%CI 1.38-2.41) for overweight mothers. The rate of high birth weight among infants from overweight mothers (aOR 1.75, 95%CI 1.15-2.65) was significantly higher than those from normal weight mothers after adjusting for known confounding factors. The rate of small for gestational age (SGA) singleton (aOR 2.37, 95%CI 1.14-4.93) was lower in mothers with underweight than mothers with normal weight. Conclusions: Maternal underweight was a significantly protective factor against LGA infant for singletons born from PCOS patients after FET, whereas maternal overweight was an adverse factor for LGA infant.